The social embedness of the underground economy - Imbrescu Ion (SZTE Gazdaságtudományi Kar közleményei, 2004)
Economic activities mean not only official activities but also the activities that belong to the so call underground economy. In this paper, I try to define the sphere of underground economy and to reveal the aspects of informal economy as part of it. Informal economy means those kinds of activities, which have predominant non-negative effects in the economic life of a country. There are several cases when informal activities belong to traditions or even culture and not to pure economy. But, if these kinds of activities are used as special events, it is possible to have a positive and stimulating role in the development of the areas where they are present. I try to reveal in this paper that several informal activities created very strong liaisons between members of small communities of Almaj Valley, liaisons, which create a process of social identification.